Hemodynamic and bispectral changes during pin insertion in craniotomy - effect of locally infiltrated bupivacaine - Vesna Durnev; Marija Soljakova; Venko Filipce; Maja Mojsova Mijovska; Marina Temelkovska Stevanovska (Macedonian Academy of Sciences and Arts, 2017)
Cranial pins insertion is a method for head stabilization and together with the scalp incision is one of the biggest noxious stimulus associated with arousal and rapid increase of the blood pressure leading to pathological increase of the intracranial pressure. The aim of this investigation is to study the superiority of the locally infiltrated anesthetic bupivacaine just before the skull pin insertion and the scalp incision in craniotomy under general anesthesia.
Keywords: cranial pin; local infiltrative anesthesia; bupivacaine